Early origin for human-like precision grasping: a comparative study of pollical distal phalanges in fossil hominins. - Sergio Almécija (Public Library of Science (PLoS), 2010)
Background The morphology of human pollical distal phalanges (PDP) closely reflects the adaptation of human hands for refined precision grip with pad-to-pad contact. The presence of these precision grip-related traits in the PDP of fossil hominins has been related to human-like hand proportions (i.e. short hands with a long thumb) enabling the thumb and finger pads to contact. Although this has been traditionally linked to the appearance of stone tool-making, the alternative hypothesis of an earlier origin--related to the freeing of the hands thanks to the advent of terrestrial bipedalism--is also possible given the human-like intrinsic hand proportion found in australopiths. Methodology/principal findings We perform morphofunctional and morphometric (bivariate and multivariate) analyses of most available hominin pollical distal phalanges, including Orrorin, Australopithecus, Paranthropous and fossil Homo, in order to investigate their morphological affinities. Our results indicate that the thumb morphology of the early biped Orrorin is more human-like than that of australopiths, in spite of its ancient chronology (ca. 6 Ma). Moreover, Orrorin already displays typical human-like features related to precision grasping. Conclusions These results reinforce previous hypotheses relating the origin of refined manipulation of natural objects--not stone tool-making--with the relaxation of locomotor selection pressures on the forelimbs. This suggests that human hand length proportions are largely plesiomorphic, in the sense that they more closely resemble the relatively short-handed Miocene apes than the elongated hand pattern of extant hominoids. With the advent of terrestrial bipedalism, these hand proportions may have been co-opted by early hominins for enhanced manipulative capabilities that, in turn, would have been later co-opted for stone tool-making in the genus Homo, more encephalized than the previous australopiths. This hypothesis remains may be further tested by the finding of more complete hands of unequivocally biped early hominins.